VARiATtONS m THE dHEMlCAL COMl*OSlTtOl4 OF THREE FRESHWATER FISHES OF BHAVANISAGAR RESERVOIR - Sreenivasan, A; Natarajan, M V (Indian Journal of Fisheries, 2011)
FAT variation in marine species of fish has been studied extensively in India(Venkataraman and Chari, 1953; Vasavan et al, 1960). But it is not knownwhether any such variations occur in freshwater fishes. Three dominantspecies of Bhavanisagar Reservoir were therefore chosen for this study, thefishes taken up being two cat fishes Wallago attu and Macrones (Mystus)aor, and a cyprinid, Barbus dubius.